Response of Wheat to Gypsum Application at Farmers Fields in Rainfed Pothwar: Wheat Response to Gypsum Application - Umair, Adnan; Iqbal Iqbal, Muhammad Nadeem; Bashir, Kashif; Hussain, Khadim; Naseem, Waqas; Sajjad, Muhammad Rafique; Mehmood, Tariq; Qadir, Ghulam (Biological Sciences - PJSIR, 2018)